Dairy heifer habituation to the milking routine: stress in the primiparous cow and its impacts on behavior and production - Kness, Danielle, author; Grandin, Temple, advisor; Pinedo, Pablo, committee member; Edwards-Callaway, Lily, committee member; Garry, Franklyn, committee member (Colorado State University. Libraries, 2023)
The transitional period surrounding parturition and onset of lactation is undoubtedly a stressful time in the life of a dairy cow. This is especially true for primiparous cows, who have no previous experience to the milking routine and must become accustomed to increased contact with human caretakers as well as the host of novel sights, sounds, smells and sensations in the milking parlor. Behaviors stemming from acute stress have the potential to increase risk of injury to parlor employees, who must be located close to the cows in order to perform their duties. Even so, the specific changes in cow behavior in the parlor over the course of the first lactation are not well documented, presenting a challenge to farm managers who wish to train employees in primiparous cow management. The main focus of this thesis is to present current research on this topic, as well as present new research regarding specific, daily changes in primiparous cow behavior during the first lactation. Chapter one is a review of the current literature regarding sources of stress in first-lactation heifers and their impacts on various aspects of cow behavior and production, as well as on worker safety and wellbeing. The roles of precision livestock farming technologies on modern dairy farms are also discussed in this chapter, as well as the potential of these technologies for dairy cow welfare management and research. The objective of chapter two is to describe the dynamics of milking unit kick-off in primiparous and multiparous cows during the first three months of lactation. Data were collected from 199 primiparous (PRI) and 670 multiparous (MUL) cows who calved between August and November of 2020. From 3 days in milk (DIM) until 90 DIM, data were downloaded daily for each cow from the farm's software program. The main variables of interest were parity category and milking machine kick-offs (KO), which were reported by the milking system when an abrupt interruption in the milk flow occurred. KO events were used in our analysis as a proxy for habituation to the milking routine, and were analyzed by DIM. We found that proportions of KO were greater in PRI than in MUL throughout the monitoring period, and that when analyzed by DIM, first-lactation cows showed a non-linear trend of kick-offs. This indicated that changes in behaviors displayed during the habituation process are not linear, but instead are more complex. Chapter 3 is an analysis of additional data that were collected during the study presented in chapter 2. Study participants were the same, but our goal in this chapter was to investigate any possible relationships between rates of machine kick off, daily changes in milk yield, and occurrence of mastitis during early lactation. Cows with varying frequencies of machine kick-offs were categorized into quartiles. Quartiles were then analyzed for potential interactions with milk yield and mastitis occurrence. Overall, we found no differences in milk yield between KO quartiles, but both primiparous and multiparous cows in the quartile with the highest KO rates had higher rates of mastitis.
Keywords: dairy cow; habituation; primiparous cow; first lactation heifer; cattle behavior; kicking